2016
DOI: 10.1007/s40801-016-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Adverse Drug Reaction Documentation upon Implementation of an Ambulatory Electronic Health Record System

Abstract: BackgroundDetection, monitoring and treatment of adverse drug reactions (ADRs) are paramount to patient safety. The use of a comprehensive electronic health record (EHR) system has the potential to address inadequacies in ADR documentation and to facilitate ADR reporting to health agencies. However, effective methods to maintain the quality of documented ADRs within an EHR have not been well studied.ObjectiveTo evaluate the accuracy and effectiveness of ADR documentation transfer throughout the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
2
8
0
Order By: Relevance
“…The results indicated that 44% of patients had incorrectly documented adverse drug reaction information in the EHR. 22 The results of our study, performed in 2 separate adult inpatient units of a community hospital, are consistent with the results of other studies performed in various settings and further clarify which medication classes are most prone to discordance.…”
Section: Discussionsupporting
confidence: 91%
“…The results indicated that 44% of patients had incorrectly documented adverse drug reaction information in the EHR. 22 The results of our study, performed in 2 separate adult inpatient units of a community hospital, are consistent with the results of other studies performed in various settings and further clarify which medication classes are most prone to discordance.…”
Section: Discussionsupporting
confidence: 91%
“…We report that the presence of a pharmacovigilance service greatly increased timely documentation of ADRs within the medical record. This is consistent with reports from other centers, after incorporation of a prospective pharmacovigilance service 3,7,8,15‐19 . Although the increased detection of ADRs after incorporation of a prospective pharmacovigilance program is well documented, these programs are unfortunately not the standard in all hospitals.…”
Section: Discussionsupporting
confidence: 89%
“…Although the increased detection of ADRs after incorporation of a prospective pharmacovigilance program is well documented, these programs are unfortunately not the standard in all hospitals. Developing standardized EMR alerts or reports to detect ADRs requires time and infrastructure 3,6,16,20,21 . In addition, personnel, typically a clinical pharmacist, are needed to evaluate automated EMR reports and investigate potential ADRs 20,22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations